Elucidating the Molecular Mechanisms of Physiological Fruit Abscission in Actinidia arguta Through Comparative Transcriptomics and Transient Genetic Transformation - Pengqiang Yuan; Yanli Wang; Yining Sun; Guoliang Liu; Hongyan Qin; Shutian Fan; Yiping Yan; Bowei Sun; Wenpeng Lu (Plants)
Actinidia arguta (A. arguta) is valued for its nutritional richness, but physiological fruit abscission severely limits production efficiency in elite cultivars. To unravel the molecular basis of this process, we compared two cultivars: abscission-prone ‘KL’ and abscission-resistant ‘JL’. During fruit development, ‘KL’ exhibited an earlier decline in auxin (AUX) levels within the fruit abscission zone (FAZ), coupled with persistently higher ethylene (ETH) concentrations and polygalacturonase (PG) activity compared to ‘JL’. Comparative transcriptomics identified abscission-related genes enriched in plant hormone signaling (AUX, ETH, ABA, JA, BR), starch/sucrose metabolism, and photosynthesis pathways. AUX signaling diverged predominantly during early development, while ETH, BR, and JA pathways varied across multiple stages. Exogenous applications of plant growth regulators (ethephon, 2,4-D, methyl jasmonate, and 2,4-epibrassinolide) and transient overexpression of key genes (AaETR1, AaERF035, AaPME68, AaPP2C27, AaMYC1, and AaPMEI10) validated their roles in modulating hormone crosstalk and cell wall remodeling. Overexpression of AaERF035 and AaPME68 likely accelerated abscission by enhancing ETH biosynthesis and pectin degradation, while AaPMEI10 and AaMYC1 potentially delayed abscission via suppression of cell wall-modifying enzymes. This study elucidates the hormonal and transcriptional networks governing fruit abscission in A. arguta, providing insights for targeted breeding and cultivation strategies to mitigate yield loss.